The six disciplines of breakthrough learning : how to turn training and development into business results - Pollock, Roy V. H.; Jefferson, Andrew McK.; Wick, Calhoun W.; Wick, Calhoun W. (Hoboken : Wiley, 2015)
'Get real results for your business - maximize your training and development programs Corporate learning and development programs play an undeniable role in successful business endeavors, but only when they're done right. The significant revisions in the third edition of The Six Disciplines of Breakthrough Learning add fresh, timely elements to a resource that has become known globally as a trusted guide for professionals determined to get the most of their companies' training and development programs. All-new examples, tools, guides, and insights combine to make an excellent, all-in-one resource for everyone from workplace professionals and HR managers to training development providers and businesses leaders looking to maximize the return on their enterprise's learning budget. Infused with current research and recent case studies, this resource serves as a practical guide that recommends concrete actions for producing tangible results. Tools, guides, and checklists in every chapter ensure that readers walk away with meaningful strategies that can be implemented right away. The book includes: A complete review of research drawn from thousands of insights, goals, and lessons learned Specific strategies and actions that can be put into effect quickly for immediate results A focus on ROI for business leaders wanting to make a clearer connection between dollars spent and new skills gained Checklists in each chapter to help learning organizations perform quality audits of new and existing learning programs The third edition of The Six Disciplines of Breakthrough Learning contains so many new resources and so much thoroughly-revised content that even those who own previous editions will find its reinvigorated approach highly beneficial. Strengthen the link between your learning efforts and your business goals with this increasingly popular, globally recognized resource'--
Machine generated contents note: Foreword ix Conrado Schlochauer Introduction: The Six Ds 1 D1 Define Business Outcomes 39 D2 Design the Complete Experience 77 D3 Deliver for Application 109 D4 Drive Learning Transfer 149 D5 Deploy Performance Support 191 D6 Document Results 223 Coda 281 Afterword 287 Will Thalheimer References 291 Name Index 305 Subject Index 309 About the Authors 323 .
Revised edition of the authors' The six disciplines of breakthrough learning, 2010.
Includes bibliographical references and index.
Keywords: Organizational learning; Employees -- Training of